Efeito da modificação térmica em escala industrial na qualidade da madeira de Tectona grandis Linn. F. - Menezes, Walmir Marques de (Universidade Federal de Santa Maria, 2018)
Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - CAPES === The process of the thermal modification on wood is the application of heat in order to improve its quality. The objective of this research was to evaluate the effect of the thermal modification in industrial scale on the wood quality of Tectona grandis Linn. F. To this end, boards of approximately 35 x 100 x 2200 mm (thickness, width and length), separated and numbered in quality classes. First-class boards were with the highest presence of core and free of defects, such as cracks, knots, warps, among others, while the second class boards presented larger portions of sapwood and defects mentioned above. In this way, four batches of wood were separated into four treatments, with T1 and T2 being the natural wood of the first and second quality respectively, and in the same order of quality, however, the T3 and T4 treatments were thermally modified. The original pieces of 2200 mm length were divided into two pieces of equal size (1100 mm), one of them corresponding to the wood control (T1 and T2), that is, the non-thermally modified, for later comparison with the treated wood (T3 and T4). The VAP HolzSysteme® thermal modification was conducted according to the program used by the company, where the final temperature was 160 ° C. After the heat treatment, the wood was tested by the quantification of defects; Effect on chemical composition; In the physical and mechanical properties, and, finally, of the resistance to xylophagous fungi. The defects were analyzed by the standard NBR 9487 (ABNT, 1986) through cracks (top and surface) and warping (bending, bending and recessing). In addition, the moisture content was also measured. The chemical analyzes followed the methodologies described in the Technical Association of Pulp and Paper Industry - TAPPI (Tappi, 1999), through the analysis of total extractives, lignin Klason, holocellulose, hemicellulose and alpha cellulose. For the physical tests (equilibrium moisture content, apparent specific mass, total swelling and swelling anisotropy), the procedures established in ASTM D 143-94 (ASTM, 2000) were used. Colorimetry followed ASTM D 2244-09a (ASTM, 2009). The test of static flexion and parallel compression of the fibers followed the standard ASTM D 143-94 (ASTM, 2000). The test of shear strength in parallel compression to the fibers in the glue line was according to ASTM D - 905 (ASTM, 2008a) and the percentage of failure of the specimens, followed the standard ASTM D - 3110 (ASTM, 2008 b). The assembly of the biological analyzes followed the recommendation of the European norm EN 113 (1996). The fungus used was Ganoderma applanatum (white rot) and the resistance was evaluated by the ASTM D 2017 standard. The heat treatment influenced the increase of the moisture content, but this did not interfere with the quality of the wood. The quality of the thermal modification was satisfactory, if evaluated by the defects of cracks and warpage. In addition, the quality of the wood was paramount for the lowest defect rate. The content of extractive and alpha cellulose increased significantly with thermal modification, in contrast, holocellulose and hemicellulose reduced, and still, for the latter, the quality of the wood may have influenced. The Klason lignin content was not significantly altered by temperature or by the quality of the wood. The equilibrium moisture content, apparent specific mass of the wood, total swelling and anisotropy of wood swelling decreased after heat treatment, due to loss of hemicellulose mass and increase of total extractives. Therefore, the dimensional stability of the wood has been increased. The colorimetry was influenced by the thermal modification of the wood, through the darkening and increase of the reddish hue. The quality of the wood did not influence the physical properties, except the colorimetry, which was altered by the difference in the proportion of the sapwood and core of the specimens. The failures in the wood caused by the shear strength in the glue line were satisfactory. The mechanical strength of all tests was reduced by the quality of the wood and the thermal modification, which in the latter case caused hemicellulose degradation. The wood was considered very resistant, although the loss of mass in contact with the fungus increased in the thermally treated wood. The results may have been influenced by the quality of the wood and the degradation of the hemicelluose. It was concluded that, in general, the effect of the thermal modification on the quality of the wood was significant in all evaluated properties (chemical, physical, mechanical and biological), and the presence of heartwood, sapwood had little influence. The main responsible for the changes in the wood after the thermal modification was the degradation of hemicellulose. === O processo da modificação térmica da madeira é a aplicação de calor a fim de melhorar a sua qualidade. O objetivo dessa pesquisa foi avaliar o efeito da modificação térmica em escala industrial na qualidade da madeira de Tectona grandis Linn. F. Para isso, foram utilizadas tábuas de aproximadamente 35 x 100 x 2200 mm (espessura, largura e comprimento), separadas e numeradas em classes de qualidade. As tábuas de primeira classe foram aquelas com a maior presença de cerne e livres de defeitos, tais como rachaduras, nós, empenamentos, dentre outros, ao passo que as de segunda classe apresentaram porções maiores de alburno e os defeitos citados anteriormente. Desta forma, foram separados quatro lotes de madeira, em quatro tratamentos sendo o T1 e T2 para a madeira natural de primeira e segunda qualidade respectivamente e, na mesma ordem de qualidade, entretanto modificadas termicamente os tratamentos T3 e T4. As peças originalmente de 2200 mm de comprimento dividiram-se em duas peças de iguais dimensões (1100 mm), sendo uma delas correspondendo à madeira testemunha (T1 e T2), ou seja, a não modificada termicamente, para posterior comparação com a tratada (T3 e T4). A modificação térmica VAP HolzSysteme® foi conduzida de acordo com o programa utilizado pela empresa, em que a temperatura final foi de 160ºC. Posteriormente ao tratamento térmico, a madeira foi testada pelo efeito na composição química; nas propriedades físicas e mecânicas e, por fim, na resistência aos fungos xilófagos. As análises químicas seguiram as metodologias descritas nas normas Technical Association of pulp and Paper Industry - TAPPI (Tappi, 1999), onde foi determinado os teores de extrativos totais, de lignina Klason, de holocelulose, de hemicelulose e de alfa celulose. Para a realização dos ensaios físicos (teor de umidade de equilíbrio, massa específica aparente, inchamento total e anisotropia de inchamento) foram utilizados os procedimentos estabelecidos na norma ASTM D 143-94 (ASTM, 2000). A colorimetria seguiu a norma ASTM D 2244-09a (ASTM, 2009). O teste de flexão estática e compressão paralela as fibras seguiram a norma ASTM D 143-94 (ASTM, 2000). O teste de resistência ao cisalhamento na compressão paralela às fibras na linha de cola foi conforme a norma ASTM D - 905 (ASTM, 2008a) e o percentual de falhas dos corpos de prova, seguiu a norma ASTM D - 3110 (ASTM, 2008 b). A montagem das análises biológicas seguiu a recomendação da norma Europeia EN 113 (1996). O fungo utilizado foi o Ganoderma applanatum (podridão-branca) e a resistência foi avaliada pela norma ASTM D 2017. O teor de extrativos e alfa celulose aumentaram significativamente com a modificação térmica, em contrapartida, a holocelulose e hemicelulose reduziram, e ainda, para esse último, a qualidade da madeira pode ter influenciado. O teor de lignina Klason não foi alterado significativamente pela temperatura e pela qualidade da madeira. O teor de umidade de equilíbrio, a massa específica aparente, o inchamento total e anisotropia de inchamento da madeira diminuíram após o tratamento térmico, devido à perda de massa da hemicelulose e aumento dos extrativos totais. Por conseguinte, elevou-se a estabilidade dimensional da madeira. A colorimetria foi influenciada pela modificação térmica da madeira, por meio do escurecimento e aumento da tonalidade avermelhada. A qualidade da madeira não influenciou nas propriedades físicas, exceto a colorimetria, que foi alterada pela diferença de proporção do alburno e cerne dos corpos de prova. As falhas na madeira causada na resistência do cisalhamento na linha de cola foram satisfatórias. A resistência mecânica de todos os testes foi reduzida pela qualidade da madeira e a modificação térmica, que neste último caso, causou a degradação da hemicelulose. A madeira foi considerada muito resistente, apesar da perda de massa em contato com o fungo ter aumentado na madeira tratada termicamente. Os resultados podem ter sido influenciados pela qualidade da madeira e a degradação da hemiceluose. Conclui-se que de maneira geral, o efeito da modificação térmica na qualidade da madeira foi significativo em todas as propriedades avaliadas (químicas, físicas, mecânicas e biológicas), sendo que, a presença de cerne, alburno tiveram pouca influência. A principal responsável pelas mudanças na madeira após a modificação térmica foi a degradação da hemicelulose.